2014
DOI: 10.2337/dc13-2939
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Among Hispanics/Latinos From Diverse Backgrounds: The Hispanic Community Health Study/Study of Latinos (HCHS/SOL)

Abstract: OBJECTIVEWe examine differences in prevalence of diabetes and rates of awareness and control among adults from diverse Hispanic/Latino backgrounds in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL).RESEARCH DESIGN AND METHODSThe HCHS/SOL, a prospective, multicenter, population-based study, enrolled from four U.S. metropolitan areas from 2008 to 2011 16,415 18–74-year-old people of Hispanic/Latino descent. Diabetes was defined by either fasting plasma glucose, impaired glucose tolerance 2 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
292
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(303 citation statements)
references
References 16 publications
9
292
0
2
Order By: Relevance
“…The AHEI was inversely associated with waist circumference, blood pressure, and glucose for Mexicans and Puerto Ricans and with TGs for Mexicans, and was positively associated with HDL cholesterol for Puerto Ricans and Central Americans. Standardized measures showed that associations 2 Physical activity was assessed by using the Global Physical Activity Questionnaire. Self-reported hours of activity at work, travel, and leisure, as well as sedentary behavior, were converted into metabolic equivalents and categorized as high, moderate, or low levels, on the basis of number of days spent doing physical activity at each designated intensity level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AHEI was inversely associated with waist circumference, blood pressure, and glucose for Mexicans and Puerto Ricans and with TGs for Mexicans, and was positively associated with HDL cholesterol for Puerto Ricans and Central Americans. Standardized measures showed that associations 2 Physical activity was assessed by using the Global Physical Activity Questionnaire. Self-reported hours of activity at work, travel, and leisure, as well as sedentary behavior, were converted into metabolic equivalents and categorized as high, moderate, or low levels, on the basis of number of days spent doing physical activity at each designated intensity level.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of diabetes in this adult population has been estimated to be between 11% (1) and 17% (2), and in 2015, 48% of Hispanic and Latino men and 32% of women had CVD (3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the genetic risk of OSA is known to vary by continental ancestries; a study of 31 global ancestral informative markers in Brazilians has indicated ancestry-related differences of risk for OSA (5). No prior study has studied the genetic associations of OSA in Hispanic/Latino Americans, a growing demographic group with a high prevalence of OSA and associated cardiovascular disease risk factors (6)(7)(8).…”
mentioning
confidence: 99%
“…While the prevalence rate of T2DM is 7.6 % among non-Hipsanic Whites age 20 and older the rate among Hispanic populations age 18-74 years is 16.9 %, exceeding that of non-Hispanic Blacks (13.2 %) and American Indians/Alaskan Natives (15.9 %) [6,7]. Among Hispanic subgroups, persons of Mexican heritage have the highest prevalence rate (18.3 %), followed by Puerto Ricans and Dominicans at 18.0.…”
Section: Introductionmentioning
confidence: 99%